2018
DOI: 10.1016/j.athoracsur.2017.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Renal Functional Reserve Predicts Risk of Acute Kidney Injury After Cardiac Operation

Abstract: Among elective cardiac surgical patients with normal resting glomerular filtration rates, preoperative RFR was highly predictive of AKI. A reduced RFR appears to be a novel risk factor for AKI, and measurement of RFR preoperatively can identify patients who are likely to benefit from preventive measures or to select for use of biomarkers for early detection. Larger prospective studies to validate the use of RFR in strategies to prevent AKI are warranted. ClinicalTrials.gov identifier: NCT03092947, ISRCTN Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 27 publications
2
70
0
1
Order By: Relevance
“…In order to overcome this limitation, the quantification of Renal Functional Reserve (RFR), a measure of the kidney's capacity to increase GFR by a combination of nephron recruitment and increases in renal blood flow coupled with hyperfiltration, has been proposed [20][21][22]. Healthy nephrons have the ability to increase filtration rate.…”
Section: Renal Functional Reservementioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome this limitation, the quantification of Renal Functional Reserve (RFR), a measure of the kidney's capacity to increase GFR by a combination of nephron recruitment and increases in renal blood flow coupled with hyperfiltration, has been proposed [20][21][22]. Healthy nephrons have the ability to increase filtration rate.…”
Section: Renal Functional Reservementioning
confidence: 99%
“…This physiological mechanism can be used to estimate a global potential nephron recruitment in order to stratify, before surgery, the possibility to tolerate renal injuries and additional loads. It has been estimated that RFR physiologically accounts for over a 30% increase in GFR [20,21]. Such determinations are easily made by determining the difference between GFR measured before and 1-2 h after eating a protein meal [20].…”
Section: Renal Functional Reservementioning
confidence: 99%
“…Furthermore, measurement of renal reserve is not yet standardized and therefore rarely performed. At present, renal reserve is measured by determining the difference between the resting and stress GFR from the endogenous creatinine CCr before and after an oral protein load consumed after an 8-h fast and accompanied by adequate oral hydration [9]. Hourly CCr measurements are used and continued for at least 3 h. Consequently, they are subject to the same constraints and limitations as short duration CCr measurements following supervised voiding [5].…”
mentioning
confidence: 99%
“…Hourly CCr measurements are used and continued for at least 3 h. Consequently, they are subject to the same constraints and limitations as short duration CCr measurements following supervised voiding [5]. Nevertheless, a recent study showed that low reserve predicted AKI following cardiac bypass with an AUC of 0.83 (95% CI 0.70-0.96) [9]. This was similar to the immediate postoperative predictive performance of the urinary cell-cycle arrest biomarkers insulin-like growth factor binding protein-7, and tissue inhibitor of metalloproteinase-2, (AUC 0.87 [95% CI 0.79-0.84]) [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation